Reacting Flow Characteristics of Wall-mounted Ramps in Strut-injection Scramjet Combustors under Varying Hydrogen Jet Pressures - A. Antony Athithan; S. Jeyakumar (Journal of Applied Fluid Mechanics)
Implications of hydrogen pressure injection variances from strut injectors in a supersonic reacting flow domain have been a focus of this study. A numerical investigation is performed using Reynolds Averaged Navier Stokes (RANS) equations in combination with the Shear Stress Transport (SST) k-ω turbulence model to understand flow mechanics at supersonic combustion. Under varying fuel jet pressures, the impact of dual ramps symmetrically placed at the scramjet combustor walls behind a strut injection is computationally investigated. The effect of hydrogen injection pressure variations in scramjet combustors is explored based on essential features including shock pattern, static pressure fluctuations, and static temperature throughout the combustor. The numerical outcomes are confirmed by experimental data and lie within a reasonable range, indicating that the simulation method may be applied to further study. Variation in fuel injection pressures affects supersonic combustion phenomena in hypersonic vehicles, according to the findings of this study. A rise in the hydrogen jet pressure accelerates flow downstream of the injector and reduces the intensity of shock wave interactions in ramp-based scramjet combustors. In addition, the present research demonstrates that an increase in hydrogen jet pressure, P5, in reactive supersonic airflow accelerates mixing and combustion, with a minimal overall pressure loss of 17% in the combustor, achieved within a shortened length of approximately 52% compared to the DLR model.